Membina Minat Kanak-kanak Membaca Kesusasteraan Satu Pandangan Ringkas - Othman, Ahmad (Penerbit Universiti Sains Malaysia, 1989)
This article attempts to discuss the development of children's reading interest, which through proper selection andguidance can cultivate good reading habits. Parents and teachers should also know how to motivate unmotivated children to read and they must offer the children reading materials dealing with more basic areas of human needs, and in order to motivate fairly interested students, they must expand the tastes of these students into books dealing with Marslow's higher level of human needs. The paper also discusses the influence of factors such as sosio-;;-conomic, genetic, environment and teaching-learning activities on the reading of the children. The types of books, especially with beautiful pictures, wide themes of real and imaginative world and the level of language suitable for children of various ages, if properly selected and taught may bring the children to closer reading and give them enjoyment and satisfaction